Hubungan Kebutuhan Perawatan Bayi BBLR di Rumah dengan Pendekatan Family Centered Maternity Care di Puskesmas Lhok Kruet Aceh Jaya - Efrida Yanti Siregar; Aminah Aminah; Dewiana Suharti; Jayanti Turnip; Herni Suryana (Malahayati Nursing Journal, 2023)
ABSTRACT Low birth weight, commonly referred to as LBW, remains a major problem in infant mortality in Indonesia. Mother's skills for optimal care for low birth weight babies by using educational experiences, discussions, as well as technology for stunting prevention learning media to increase mother's knowledge and confidence to care for babies with low birth weight can be strengthened through Family- Centered Maternal Care (FCMC), which is care focused on a family that provides care to women and their families, integrating pregnancy, childbirth and infant care into the chain of family life. FCMC was implemented to improve self-care and newborn care skills. The purpose of this study is to find out whether there is a relationship between the care needs of LBW infants at home and the FMCM approach. This research will use a descriptive method with a cross sectional approach, will be carried out at the Lhok Kruet Health Center, Kec. Sampoiniet Kab. Aceh Jaya, held in July 2022. All populations were sampled, namely 30 mothers, the type of research was descriptive with a cross sectional approach. The results of the chi square test obtained a p-value of 0.002 (pα) 0.05, namely Ho is rejected and Ha is accepted, the conclusion is that there is a relationship between the care needs of LBW babies at home with the Family Centered Maternity Care approach at the Lhok Kruet Health Center Aceh Jaya 2022.  Keywords: Needs, LBW, Family Centered Maternity Care  ABSTRAK Berat bayi lahir rendah yang biasa disebut sebagai BBLR tetap menjadi masalah utama kematian bayi di Indonesia. Kemahiran ibu agar perawatan optimal pada BBLR dengan menggunakan pengalaman pendidikan, diskusi, juga teknologi untuk media pembelajaran pencegahan stunting untuk bertambahnya pengetahuan dan kepercayaan diri ibu untuk merawat bayi dengan berat badan kurang dapat diperkuat melalui Family-Centered Maternal Care (FCMC) ialah perawatan berfokus terhadap keluarga yang memberikan perawatan kepada wanita serta keluarganya, menyatukan kehamilan, persalinan dan perawatan bayi ke dalam rantai kehidupan keluarga. FCMC diimplementasikan supaya meningkatkan keterampilan perawatan diri dan perawatan bayi baru lahir. Tujuan penelitian ini agar mengetahui adakah hubungan kebutuhan perawatan bayi BBLR di rumah dengan pendekatan FMCM?. Pada penelitian ini akan menggunakan metode deskriptif dengan pendekatan cross sectional, akan dilaksanakan di Puskesmas Lhok Kruet Kec. Sampoiniet Kab. Aceh Jaya, diadakan pada Juli 2022. Semua populasi dijadikan sampel yaitu 30 orang ibu, jenis penelitan yaitu deskriptif dengan pendekatan cross sectional. Hasil uji chi square diperoleh nilai p-value 0,002 (pα) 0,05 yaitu Ho ditolak dan Ha diterima, kesimpulannya terdapat hubungan kebutuhan perawatan bayi BBLR di rumah dengan pendekatan Family Centered Maternity Care di Puskesmas Lhok Kruet Aceh Jaya 2022. Kata Kunci: Kebutuhan, BBLR, Family Centered Maternity Care